L’impact de la coopération culturelle française sur la langue - ALASSAF, Yaqdhan (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
This review is concerned with the cultural and scientific cooperation between Iraq and France. Through this cooperation the French government provided joint fellowship program in master and doctorate in various subjects. With regard to teaching French as a second foreign language the support included training courses (2-4 weeks) offered to French language teachers to help keep them abreast of the development of the language education sector. In addition, free curricula taught in the French language departments in five Iraqi universities has also been provided through this cooperation. Recently, in October 2017 the French government affirmed their continued willingness and commitment to participate in the rehabilitation of higher education in general and specifically revitalization of linguistic centers by signing a Goodwill Memorandum. This review, explores possible benefits to a country like Iraq, which has suffered for years from being away from development and advancement as well as the destruction of infrastructure.